Mulheres do Poti: transformação cerâmica e representações femininas no Poti Velho, Teresina, Piauí: Poti Women: ceramic transformation and female representations in Poti Velho, Teresina, Piauí (Revista de História da UEG (REVHIST), 2020)
This article proposes to understand the ceramic transformations of Poti Velho and female representations in the clay pieces of COOPERART-Poty, in Teresina, Piauí. To carry out the study, we used oral methodology, newspapers and photographs, in addition to field research to access ceramic objects. We seek to understand that transformations take place in Poti Velho ceramics, in addition to the existing relationships between cultural identity, social memory and material culture. We noticed that the pieces change as women master the ceramic work and develop a work that shows their identities, memories and life stories as a social group. The set of ceramic pieces by Poti Women represents the women inhabitants of Poti Velho: the potter, the ceramist, the fisherwoman, the religious and the women of beads. Keywords: Women. Ceramics. Representations. Teresina.